EXPLORING THE DYNAMICS OF TECHNOSTRESS, PERCEIVED ORGANIZATIONAL SUPPORT, AND WORK ENGAGEMENT IN HIGHER EDUCATION INSTITUTIONS - Ni Putu Cempaka Widyawati; I Made Artha Wibawa (CV. Adiba Aisha Amira, 2026)
The rapid integration of digital technologies in higher education has transformed academic and administrative processes, but it has also given rise to new challenges such as technostress among faculty and staff. This study explores the interrelationships between technostress, perceived organizational support, and work engagement within higher education institutions. Drawing on organizational behavior and occupational stress frameworks, the research investigates how technostress influences employees’ psychological states, and whether perceived organizational support can serve as a buffer that enhances engagement. Using a quantitative approach with survey data collected from academic and administrative staff, the study applies structural equation modeling to test the hypothesized relationships. The findings reveal that technostress negatively impacts work engagement, while perceived organizational support significantly mitigates this effect and fosters higher levels of engagement. These results highlight the critical role of supportive organizational practices in sustaining employee well-being and performance amidst ongoing digital transformation. The study contributes to the literature on technology-related stressors in educational settings and provides practical insights for institutional leaders seeking to cultivate a resilient and engaged workforce.